Endemic medicinal plants of Ethiopia: Ethnomedicinal uses, biological activities and chemical constituents. (15th July 2022) - Ayalew, Hiwot; Tewelde, Eyael; Abebe, Besufekad; Alebachew, Yonatan; Tadesse, Solomon
Abstract: Ethnopharmacological relevance: Around 80% of Ethiopians rely on traditional medicinal plants to treat a variety of ailments, and the country is home to a number of endemic plants, making it part of East Africa's hotspot of biodiversity. Despite widespread acceptance of endemic medicinal plants among the local community, comprehensive documentation of their therapeutic uses and phytochemistry is lacking. This review thus provides the first comprehensive appraisal of traditional use, pharmacological properties and phytochemistry of Ethiopian endemic medicinal plants. By storing and preserving indigenous and scientific knowledge about the medicinal benefits of the plants, such documentation generates information database for the future. It also aids the conservation of key medicinal plants along with translational research to accelerate the development of pharmaceuticals. Aim of the review: The aims of this review are to collect and document current information on the ethnopharmacological uses, phytochemistry, and biological activities of Ethiopian endemic medicinal plants, identify research gaps, and provide perspectives and suggestions for future research on the plants as potential sources of pharmaceuticals. Materials & methods: A comprehensive literature review using electronic databases such as Medline, Web of Science, Google Scholar, ScienceDirect, SpringerLink, and Wiley Online Library was conducted for collecting relevant information. The World Flora Online (WFO) database and the International Plant Names Index (IPNI) were utilized to authenticate the taxonomic information of the plants. Chemical structures were drawn using ChemBioDraw Ultra 12.1 and verified via PubChem. Results: The present review has identified 412 Ethiopian endemic plants. Out of the 412 endemic plants species recorded for Ethiopia 44 are medicinally valuable to mitigate a myriad of diseases, and nine (27.3%) of them are endangered. Our literature survey also found out that a total of 74 compounds were isolated and characterized from the endemic plants, with phenolics accounting for the majority of them (66.2%). The plants exhibited antimalarial, antimicrobial, anticancer, anthelmintic, mosquitocidal, antidiabetic, antioxidant, and anti-inflammatory properties. Conclusion: The work has resulted in an up-to-date inventory of Ethiopia's endemic flora, as well as the identification of species with traditional medicinal uses. The pharmacological activity and phytochemistry of numerous endemic plants with various traditional therapeutic claims are yet to be researched scientifically. Scientific validation of the herbal remedies, including evidence-based safety and efficacy studies are, therefore, crucial. The endangered medicinal plants must be conserved in order for local communities to have access to them in the future. Graphical abstract: Image 1 Highlights: Ethiopia is part of the biodiversity hotspot in the Horn of Africa. There are 44 Ethiopian endemic medicinal plants for which ethnopharmacological report is available. Antimalarial and antibacterial properties are the most common pharmacological actions investigated for the plants. Ethiopian endemic plants have yielded about 74 chemical components belonging to structurally distinct classes. Nine of the indigenous medicinal plants are on the verge of extinction.